Features of cadastral accounting and monitoring of water facilities in Ukraine - Petrakovska, Olga; Dubnytska, Marharyta (Transfer of innovative technologies, 2018)
Presents the peculiarities and problems of water bodies cadastral account in Ukraine. The results of analyses the regulatory framework in the field of water bodies monitoring and account in cadastre are presented. Authors compare ap-proaches to the water objects classification of Ukrainian and European legislation and the sci-ence of hydrology. The article presents a con-solidated list of types of water bodies with defi-nitions in terms of cadastre. Authors consider objects classification of the cadastral systems according to their dimension, that is, the ability to simulate the real world object in a certain amount of spatial-temporal measurements. The system of water management authorities in Ukraine and distribution of responsibilities between them are also analyzed. Authors identi-fied some problems such as mutual duplication of functions, and sometimes even conflicts over the division of powers between different execu-tive bodies. The system of water objects state registration in Ukraine according to the current legislation is formalized. In particular, the sys-tems for water objects account in Ukraine are analyzed in detail. Authors have sent information requests for public information to the authorities, that man-age State Water Cadastre in Ukraine (the State Agency of Water Resources of Ukraine, the State Service of Ukraine for Emergency Situa-tions, the State Service of Geology and Subsoil of Ukraine). On the basis of responses analysis the status of State Water Cadastre in Ukraine is investigated and its ability to carry out manage-rial tasks is evaluated. It is proved that water bodies account in existing two-dimensional ca-dastral systems in principle cannot be complete and adequate, as water objects are three-dimensional in nature. Finally, authors recommend to develop a single, three-dimensional monitoring and account system for water objects in Ukraine.